THE EFFECT OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE (CASE STUDY OF THE KARYA MANDIRI COOPERATIVE, WEST BANDUNG REGENCY) - Titto Rohendra; Evril Yanto Sitorus (SEAN Institute, 2023)
This study aims to determine the effect of leadership style and work discipline partially and simultaneously on employee performance at the Karya Mandiri Cooperative, West Bandung Regency. The approach used in this study is a descriptive approach, the sample of this study was taken from the entire population of employees at the Karya Mandiri Cooperative, which totaled 37 employees. Data collection techniques used by the method of questionnaires and interviews. The data analysis technique in this study uses multiple linear regression, as well as the coefficient of determination. The results of this study indicate that partially, leadership style has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Simultaneously, leadership style and work discipline have a positive and significant effect on employee performance at the Karya Mandiri Cooperative, West Bandung Regency.